Change of physical, psychological status through rapid weight loss in national judo athletes - Kim, H. C.; Park, K. J.; Bae, M. J.; Kim, Y. R. (Journal of International Academy of Physical Therapy Research, 2018)
The present study aimed to investigate rapid weight loss (RWL) and consequent physical and psychological challenges among judo athletes at the national athlete training center in 2017. The following results were obtained. Judo athletes used weight loss methods such as "gradually reduce meal portion," "skip meals," "limit water intake," "wear sweat suit for training," and "use sauna," and had physical and mental distress from such unhealthy weight management practices. Information about weight loss was obtained from "colleagues or senior athletes," "Internet," and "head coach or coach," and not experts such as nutritionists or physicians. Thus, athletes are recommended to employ healthy weight control methods based on advice from experts, such as nutritionists and physicians